2020
DOI: 10.1007/s00153-020-00713-y
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Lyndon interpolation property in propositional modal logics

Abstract: We introduce and investigate the notion of uniform Lyndon interpolation property (ULIP) which is a strengthening of both uniform interpolation property and Lyndon interpolation property. We prove several propositional modal logics including K, KB, GL and Grz enjoy ULIP. Our proofs are modifications of Visser's proofs of uniform interpolation property using bounded bisimulations [33]. Also we give a new upper bound on the complexity of uniform interpolants for GL and Grz. * kurahashi@n.kisarazu.ac.jp recently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…For each y / ∈ Range(I ′ ) such that ρR ′ y, there is x such that (y, x) ∈ P and •d : ξ ∈ ℧ y,x because Θ y,x ⊇ Θ ∋ ξ. Hence, M ′ , y ξ by IH (16). Finally, for each x / ∈ Range(I ′ ) such that not ρR ′ x, there is y such that (y, x) ∈ P and d : ξ ∈ ℧ y,x because Φ y,x ⊇ Φ ∋ ξ.…”
Section: Whenmentioning
confidence: 88%
See 1 more Smart Citation
“…For each y / ∈ Range(I ′ ) such that ρR ′ y, there is x such that (y, x) ∈ P and •d : ξ ∈ ℧ y,x because Θ y,x ⊇ Θ ∋ ξ. Hence, M ′ , y ξ by IH (16). Finally, for each x / ∈ Range(I ′ ) such that not ρR ′ x, there is y such that (y, x) ∈ P and d : ξ ∈ ℧ y,x because Φ y,x ⊇ Φ ∋ ξ.…”
Section: Whenmentioning
confidence: 88%
“…It strengthens the Craig interpolation property (CIP) by making interpolants depend on only one formula of an implication, either the premise or conclusion. A lot of work has gone into proving the UIP, and it is shown to be useful in various areas of computer science, including knowledge representation [16] and description logics [24]. Early results on the UIP in modal logic include positive results proved semantically for logics GL and K (independently in [9,31,34]) and negative results for logics S4 [10] and K4 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Uniform Lyndon interpolation (ULIP) is a strengthening of UIP in which the interpolant respects the polarity of propositional variables (a definition follows in the next section). It first occurred in [10], where it was shown that several normal modal logics, including K and KD, have that property. In this paper we show that the non-normal modal logics E, M, EN, MN, MC, K, their conditional versions, CE, CM, CEN, CMN, CMC, CK in addition to CKID have uniform Lyndon interpolation and the interpolant can be constructed explicitly from the proof.…”
Section: Introductionmentioning
confidence: 99%
“…Visser provided purely semantic proofs for K, GL, and IPC based on bounded bisimulation up to atomic propositions [31]. This method was later applied to prove the stronger Lyndon UIP for a wide range of modal logics [17]. The semantic interpretation of uniform interpolation is called bisimulation quantifiers, see [7] for an extended explanation.…”
Section: Introductionmentioning
confidence: 99%